HEALTH CONDITION OF ADULT POPULATION OF UKRAINE AS A PROBLEM OF THE CIVIL HEALTH SYSTEM (REGIONAL ASPECT) - Skyba, O.O.; Pshenychna, L.V.; Liannoi, M.O.; Lianna, O.V. (World of Medicine and Biology, 2019)
In recent decades, the health status of people living in the WHO European Region has generally improved, but there are population groups and geographic regions with unstable socio-economic and environmental factors lagging behind by their population’s health indicators. Ukraine belongs to the countries of the European region with unsatisfactory health indicators, low average life expectancy. According to the decree of the Cabinet of Ministers of Ukraine dated November 30, 2016 No. 1002-r “On Approval of the Concept of Development of the Public Health System”, it has been determined that the public health system as a basis for preventive medicine should envisage the main measures in the field of health care and be aimed at maintaining health of the population. In this regard, the assessment of the population’s health status is one of the main prerequisites for the planning of treatment and prevention measures, substantiation of forms and methods for the network of health facilities, the efficacy assessment of work on preserving and strengthening the population’s health, which determines the relevance of the present study. The purpose of the study was to analize the health status of the adult population of Ukraine (primary morbidity, prevalence of diseases by major classes of diseases by ICD-10) in the dynamics of 2008 - 2017 on the example of Sumy region. The research material included statistical reports on the health status of the Ukraine’s population and that of the Sumy region, conceptual documents on the national health system reform and documents of international organizations. In this work analytical, statistical methods of research, method of system approach and comparative analysis are used. In the structure of the diseases prevalence among the adult population of the Sumy region, diseases of the circulatory system (33.56%) prevail in the main classes of diseases in 2017, as in previous years. The second place was occupied by diseases of the respiratory system (16.39%), the third place was formed by the diseases of the digestive system (10.01%), the fourth and fifth - diseases of the endocrine system (5.80%) and diseases of the eye and adnexa (5.38 %) and the genitourinary system (5.38%) respectively. Thus, over the past two years, the prevalence of diseases among the adult population of the Sumy region and the incidence rate of the adult population of the region have increased in 2008 and 2013, which coincides with the indices at the national level. The aforementioned fact indicates that existing problems in the field of public health pose a threat to the national security of the state and require urgent solution at the level of centers of primary medical (medical-sanitary) assistance, individual GPs of general practice - family doctors. Steady changes tendencies were established in the health status of adult population in the Sumy region, which are manifested by a high level of disease prevalence and morbidity. Over the past five years, the prevalence of diseases and morbidity in the adult population of the Sumy region has increased by 5.55% and 3.21%, respectively. Negative trends in the prevalence of diseases are manifested predominantly by an increase in the proportion of neoplasms, circulatory diseases, the digestive system diseases, compared to the similar indices in 2008 and 2013. The level of the population’s morbidity grows due to an increase in the specific gravity of the respiratory class diseases, injuries, poisonings and some other consequences, due to the effects of external factors, as well as skin and subcutaneous tissue diseases.